Androgen receptor signaling and spatial chromatin organization in castration-resistant prostate cancer - Zhou, Tianyi; Feng, Qin (Frontiers in Medicine, 2022)
Prostate cancer is one of the leading causes of cancer death and affects millions of men in the world. The American Cancer Society estimated about 34,500 deaths from prostate cancer in the United States in year 2022. The Androgen receptor (AR) signaling is a major pathway that sustains local and metastatic prostate tumor growth. Androgen-deprivation therapy (ADT) is the standard of care for metastatic prostate cancer patient and can suppress the tumor growth for a median of 2–3 years. Unfortunately, the malignancy inevitably progresses to castration-resistant prostate cancer (CRPC) which is more aggressive and no longer responsive to ADT. Surprisingly, for most of the CPRC patients, cancer growth still depends on androgen receptor signaling. Accumulating evidence suggests that CRPC cells have rewired their transcriptional program to retain AR signaling in the absence of androgens. Besides AR, other transcription factors also contribute to the resistance mechanism through multiple pathways including enhancing AR signaling pathway and activating other complementary signaling pathways for the favor of AR downstream genes expression. More recent studies have shown the role of transcription factors in reconfiguring chromatin 3D structure and regulating topologically associating domains (TADs). Pioneer factors, transcription factors and coactivators form liquid-liquid phase separation compartment that can modulate transcriptional events along with configuring TADs. The role of AR and other transcription factors on chromatin structure change and formation of condensate compartment in prostate cancer cells has only been recently investigated and appreciated. This review intends to provide an overview of transcription factors that contribute to AR signaling through activation of gene expression, governing 3D chromatin structure and establishing phase to phase separation. A more detailed understanding of the spatial role of transcription factors in CRPC might provide novel therapeutic targets for the treatment of CRPC.